ARI updates 2015 / Accounting Research Institute (Accounting Research Institute (ARI), 2015)
The Accounting Research Institute (ARI) was initially formed as a special interest group in 2002. It is an initiative with the aim to pave the pathway for a systematic and robust research in accounting in areas such as the practice and theory of financial accounting, financial criminology, corporate governance, management accounting, financial reporting, public sector accounting, taxation and accounting information system. Over the years and through thick and thin, ARI has advanced from merely a special interest group and becomes a research centre before soaring up to be the research institute that it is now.